Local food in Iceland : Identifying behavioral barriers to increased production and consumption - Halldórsdóttir, Thorhildur Ósk; Nicholas, Kimberly A. (Environmental Research Letters, 2016)
Increased production and consumption of local food may reduce the negative environmental, social, and economic impacts of industrialized and globalized food production. Here we examined potential barriers to increasing production and consumption of food produced in Iceland. First, we developed a new framework to address the behaviors of production and consumption simultaneously, to comprehensively analyze their potential barriers. We examined structural barriers by estimating the food production capacity of Iceland, and cultural and personal barriers through survey data on cultural norms and purchasing behavior from Matís, a research and development company. We found no structural barriers preventing Iceland from increasing production of local cereals, which would compliment current local production of meat and dairy and reduce reliance on imports, currently at 50% of the daily caloric intake. However, if food production became entirely local without changing the current mix of crops grown, there would be a 50% reduction in diversity (from 50 to 25 items in eight out of ten food categories). We did not identify any cultural barriers, as survey results demonstrated that consumers hold generally positive worldviews towards local food, with 88% satisfied with local food they had purchased. More than two-thirds of consumers regarded supporting the local farmer and considerations such as environmentally friendly production, fewer food miles, lower carbon footprint as important. However, they rated the local food they have access to as lower in meeting sustainability criteria, showing that they make justifications for not choosing local food in practice. This is a personal barrier to increased consumption of local food, and implies that marketing strategies and general knowledge connected to local food in Iceland might be improved. Although the results apply to the case of Iceland, the method of identifying behavioral barriers to change is applicable to other countries, regions, or foodsheds interested in assessing ...